How Does Human Capital Spillover Inflow of Foreign Workers Affect Economic Growth? - Lestari, Etty Puji; Caroline, Caroline (Frontiers in Sociology, 2021)
The ASEAN Economic Community (AEC) provides opportunities for foreign workers to enter Indonesia, including Central Java Province. The existence of these foreign workers tends to negatively and positively impact the regional economic growth of the country. Therefore, this study aims to analyze the effects of foreign workers' human capital spillover inflow on the economic growth of Central Java. A Euclidean distance spatial weights matrix was used to calculate the Spatial Autoregressive Model from 2015 to 2020. These results indicate that skilled foreign workers positively impact increasing economic growth in Central Java Province. The influx of foreign workers, along with the influx of investment, encourages local workers to follow the performance of foreign workers. This study suggests a policy to encourage technology transfer from foreign workers to local workers. The government is also expected to strengthen local workers' productivity to compete with foreign workers.